Innovation Strategy of Raw-Materials Companies in Conditions of Uncertainty on European Market of Gas (illustrated by the company ‘Gasprom’) - L. L. Razumnova; E. G. Lisovskaya (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
Today's international and national companies develop in conditions of high uncertainty, which requires flexible strategies, fast decision-making and spread of adopted strategy to all levels and spheres of the company work. Thus it is necessary to develop a non-standard combination of strategic decisions and to use more energetically theoretical achievements in the field of theory of forecast in such conditions. Support of Russian raw-materials companies that have a serious export component depends greatly on successful foresting of the market situation. The article analyses the evolution of price strategy of the company 'Gasprom' after adoption of the Third Power Package by the EU in 2009 and proposes theoretical tools for devising the effective price strategy in the long-term period. The authors ground the necessity to formulate a new long-term price export policy of the company 'Gasprom' in conditions of uncertain future demand on European market. They describe in detail and put forward for practical use in strategic planning of the company the model of making efficient managerial decisions for different levels of uncertainty of gas market, which could strengthen 'Gasprom' standing on European market and cut finance losses in tough competitive struggle.